PENGARUH STRATEGI PAIKEM GEMBROT DAN MINAT BACA TERHADAP KEMAMPUAN MENULIS PETUNJUK (SISWA KELAS VIII SMP N 1 TEMON, KULON PROGO) - Primasari Wahyuni (Pendidikan Bahasa dan Sastra Universitas Muhammadiyah Purworejo, 2015)
ABSTRACT: This research has aim prove that: (1) whether skill writing the direction of the student taught through Paikem Gembrot strategy is better than writing the direction student taught with conventional strategy; (2) wether writing the direction the student who have high reading interest is better than writing the direction skill of the children whose reading interest is low; (3) wether there is an interaction between learning strategy with the reading interest in influencing writing the direction skill of the children. The research method used is experimental. Subject of this research is private Junior High School in Temon, Kulon Progo. There are 80 students ie VIIIA and VIIIB class. The sampling technique used is through Multistage Random Sampling technique. The technique of data collection about writing the direction skill is done through practical test, and for the reading interest data uses questionnaire with Likert Scale. The technique of data analysis uses Two-Way Variance Analysis. The validity test of reading interest is done with Product Momen formula, while the reliability test is done by Alpha Cronbach formula. The result of the research: (1) the average score of writing the direction skill of the student with Paikem Gembrot strategy is different with the conventional strategy, each 8,43 and 6,29. The result of the inferential statistic analysis Fh has amount 182,70 ˃ Ft has amount 3,967 with the significance level of 5% stating that writing the direction of the student taught by Paikem Gembrot strategi is better than that of the students tight with conventional strategy, (2) The group of students whose reading interest is low and the group of students with high reading interest is different because it was influenced by the learning strategy. The group of students who have high reading interest has th lowest score of 5,40; while the highest scire is 9,63, meanwhile the group of students whose reading interest is low has a lowest score 5,30; while the highest score is 9,60. There is no interaction between learning strategy with the reading interest, it can be seen from the result of Fh which has amount of 2,71 ˂ Ft which has amount of 3,967. Keyword: paikem gembrot strategy, reading interest, and writing the direction ABSTRAK: Penelitian ini bertujuan untuk membuktikan bahwa (1) kemampuan siswa menulis petunjuk yang diajar dengan strategi Paikem Gembrot lebih baik dibandingkan dengan kemampuan siswa menulis petunjuk yang diajar dengan strategi konvensional; (2) kemampuan siswa menulis petunjuk yang memiliki minat baca lebih tinggi lebih baik dibandingkan dengan kemampuan siswa menulis petunjuk yang memiliki minat baca rendah; (3) terdapat interaksi antara strategi pembelajaran dan minat baca dalam mempengaruhi kemampuan siswa menulis petunjuk. Penelitian ini merupakan penelitian eksperimen. Subjek penelitian adalah siswa SMP Negeri 1 Temon, Kulonprogo sebanyak 80 siswa, yaitu kelas VIIIA dan VIIIB. Pengambilan sampel menggunakan teknik Multistage Random Sampling. Teknik pengumpulan data kemampuan menulis petunjuk menggunakan tes praktik. Data minat baca menggunakan angket dengan skala Likert. Teknik analisis data menggunakan Analisis Variansi Dua Jalur. Uji validitas angket minat baca dengan rumus Product Moment, sedangkan uji reliabilitas angket minat baca dengan rumus Alpha Cronbach. Hasil penelitian menunjukkan bahwa (1) skor rata-rata kemampuan siswa menulis petunjuk dengan strategi Paikem Gembrot berbeda dengan strategi konvensional, dengan nilai masing-masing 8,43 dan 6,29. Perolehan hasil analisis statistik inferensial Fh sebesar 182,70 ˃ Ft sebesar 3,967 dengan taraf signifikansi 5%. Hal tersebut menunjukkan bahwa kemampuan siswa menulis petunjuk yang diajar dengan strategi Paikem Gembrot lebih baik daripada yang diajar dengan strategi konvensional. (2) kelompok siswa yang memiliki minat baca tinggi dan yang memiliki minat baca rendah berbeda karena dipengaruhi oleh strategi pembelajaran. Nilai terendah 5,40 dan nilai tertinggi 9,63 untuk kelompok siswa yang memiliki minat baca tinggi, sedangkan nilai terendah 5,30 dan nilai tertinggi 9,60 untuk kelompok siswa yang memiliki minat baca rendah. (3) tidak terdapat interaksi antara strategi pembelajaran dan minat baca dalam mempengaruhi kemampuan menulis petunjuk, dengan perolehan hasil Fh sebesar 2,71 ˂ Ft sebesar 3,967. Kata kunci: paikem gembrot, minat baca, kemampuan menulis petunjuk